Monostotic Fibrous Dysplasia in the Humerus. Case Report - Yanett Morejón Trofimova; Yovanny Ferrer Lozano; Daniel Díaz de la Paz (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2015)
The fibrous Dysplasia is a metabolic osseous disease characterized by an accelerated osseous reabsorption, followed by the formation of an osseous womb incremented and disorganized of uncertain origin. The most frequent clinical manifestation is the continuous pain at the damaged zone. It is diagnosed for the clinic, radiological studies and the use of biochemical scoreboards. It is treated with bisphosphonates, indicated in cases with clinical manifestations and in those without symptoms in the ones that evidence areas of activity. A patient with a background of posttraumatic pain in the right elbow of a month of evolution unanswered to the treatment, he was diagnosed in the X-ray picture of third distal part of straight humerus, lithic injuries, without rupture of the cortical, with marked periostatic reaction, without radiological or ganmagraphic findings of lesion to other levels. The value of the alkaline phosphates in 1790 mmol/l corroborated the diagnosis of monostotic fibrous dysplasia in the humerus. The appropriate presentation was decided for the uncommon of this localization.